Open access policymaking: roles for academic librarians as “change agents” in research institutions - Mullen, Laura Bowering; Otto, Jane Johnson (Qualitative and Quantitative Methods in Libraries, 2017)
Many institutions have voted to pass open access policies.  It has often been stated that a “faculty champion” needs to be identified in order for any policy to move successfully through various university stakeholder groups.  Librarians have been warned not to make open access a “library issue.”  At the same time, academic librarians already possess demonstrated expertise in repository development, have established liaison relationships with departmental faculty, and are most likely to have deep knowledge of scholarly communication and publishing trends.  Librarians can leverage this expertise and experience by taking on open access leadership roles in the wider institution.  Academic librarians can become true change agents in the transformation of institutional scholarly communication practices.  Rutgers, The State University of New Jersey, working through a small Senate open access subcommittee with librarian leadership provided by the authors, successfully passed an open access policy resolution in October, 2012.